Modulating Polaron Behavior in PM6 Blends with Nonfullerene and Fullerene Acceptors: The Importance of Singlet Energy Transfer - Rebecca Harris; Chia‐Yu Chang; Junjun Guo; Hristo Ivov Gonev; Tracey M. Clarke (Advanced Materials Interfaces)
Abstract Non‐fullerene acceptors are paving the way toward high‐efficiency organic photovoltaics. In the quest to both understand the origins of these high efficiencies and to push them ever higher, the interactions between the different excited states that contribute to device function ineeds to be understood. In this work, the presence and behavior of bimodal polarons are investigated in high‐performing conjugated polymer PM6 and its blends with non‐fullerene acceptor ITIC‐4F and fullerene acceptor PC60BM. Transient absorption spectroscopy is used to gain insight into the blends’ polarons as a function of blend ratio. Two types of polymer polaron are identified in the PM6:fullerene blends: bound polarons located in pure polymer domains and “interfacial” polarons located in mixed domains. In contrast, the PM6 polarons observed in PM6:ITIC‐4F blends show very different behavior, most notably an almost complete lack of the bound polarons. This loss is attributed to efficient singlet energy transfer from donor to acceptor prior to charge photogeneration taking place. This energy transfer suppresses the formation of bound polaron pairs that rapidly decay back to the ground state, thereby providing another pathway that enables high efficiencies in non‐fullerene acceptor‐based organic photovoltaics.